Experimental investigations of effects of cooling/non cooling of EGR on two level of compression ratio in a common rail diesel engine - Gajarlawara Nilesh (Thermal Science, 2015)
EGR cooling is followed for many years and proven as an efficient technique for reducing NOx-PM emissions. EGR cooling helps in emission reduction of NOx and PM. But, it brings associated issues like cooler fouling; misfiring in cold condition, if cooling is not bypassed, during cold start. Also, it increases HC and CO emissions thus leading to increased loading of diesel oxidation catalyst. In the present study, two engine operating points were chosen from EUDC part of modified NEDC cycle for India. The two set of compression ratios were prepared. The NOx-PM along with HC and CO emissions were measured with 18.5CR. The emissions with cooled EGR were taken first which form the base optimization. The cooler was removed from the EGR circuit and same measurements were done. In the third step, the increased NOx due to non-cooled EGR was brought to the original value by increasing the Injection rail pressure and EGR rates simultaneously. In this process, the PM emission was found to be increasing marginally from its optimized value. The same experimentation was repeated for the 16.5 compression ratio. Both the compression ratios exhibit the similar trends of emissions. The magnitude of NOx PM, HC and CO differs for both the compression ratios. In order to meet the baseline optimized NOx-PM emissions with prime objective to get rid of EGR cooler and gain cost saving, reduced compression ratio found to be promising solution. There was marginal increase in CO and HC emission with this approach.